Influence of the shear stress and salinity on Anammox biofilms formation: modelling results - Isaac Fernández (2014)
Anammox biomass has a long duplication time and low yield, thus the process must be operated in reactors with good sludge retention, such as biofilm systems. Therefore, it would be important to research the ability of Anammox biomass to form biofilms under different conditions. The effects of shear stress and salinity (NaCl and CaCl2) on Anammox biofilm formation were studied. Anammox bacteria showed good attachment capacity, with an initial adhesion phase lasting for 5-7 days at the different flow rates tested (Reynolds numbers 54, 63, 188 and 400). A four-parameter model was developed and the experimental data fitted well into the model. The presence of 5 g/L of each of the two salts favoured the formation of Anammox biofilm. The effects of CaCl2 were stronger than those caused by NaCl. 15 g/L of NaCl was detrimental for the biofilm, probably due to an inhibitory effect.